Physical and biological controls on anthropogenic CO2 sink of the Ross Sea - Ingrosso, Gianmarco; Giani, Michele; Kralj, Martina; Comici, Cinzia; Rivaro, Paola; Budillon, Giorgio; Castagno, Pasquale; Zoccarato, Luca; Celussi, Mauro (Frontiers in Marine Science, 2022)
The Antarctic continental shelf is known as a critical anthropogenic CO2 (Cant) sink due to its cold waters, high primary productivity, and unique circulation, which allow it to sequester large amounts of organic and inorganic carbon into the deep ocean. However, climate change is currently causing significant alteration to the Antarctic marine carbon cycle, with unknown consequences on the Cant uptake capacity, making model-based estimates of future ocean acidification of polar regions highly uncertain. Here, we investigated the marine carbonate system in the Ross Sea in order to assess the current anthropogenic carbon content and how physical–biological processes can control the Cant sequestration along the shelf-slope continuum. The Winter Water mass generated from convective events was characterized by high Cant level (28 µmol kg−1) as a consequence of the mixed layer break-up during the cold season, whereas old and less-ventilated Circumpolar Deep Water entering the Ross Sea revealed a very scarce contribution of anthropogenic carbon (7 µmol kg−1). The Cant concentration was also different between polynya areas and the shelf break, as a result of their specific hydrographic characteristics and biological processes: surface waters of the Ross Sea and Terra Nova Bay polynyas served as strong CO2 sink (up to −185 mmol m−2), due to the remarkable net community production, estimated from the summertime surface-dissolved inorganic carbon deficit. However, a large amount of the generated particulate organic carbon was promptly consumed by intense microbial activity, giving back carbon dioxide into the intermediate and deep layers of the continental shelf zone. Further Cant also derived from High-Salinity Shelf Water produced during winter sea ice formation (25 µmol kg−1), fueling dense shelf waters with additional input of Cant, which was finally stored into the abyssal sink through continental slope outflow (19 µmol kg−1). Our results suggest that summer biological activity over the Ross Sea shelf is pivotal for the shunt of anthropogenic CO2 between the organic and inorganic carbon pools, enhancing the ocean acidification of the upper mesopelagic zone and the long-term Cant sequestration into the deep ocean.